WS4GEE: Enhancing geospatial web services and geoprocessing workflows by integrating the Google Earth Engine. (March 2023) - Liang, Jianyuan; Jin, Fengying; Zhang, Xianyuan; Wu, Huayi
Abstract: Geospatial web services (GWSs) assist scientists developing models online. Cloud computing technologies have created opportunities for faster and more efficient environmental modeling. Among of the new public cloud products, Google Earth Engine (GEE) is particularly well adapted to meet the needs of environmental scientists developing and sharing their models. However, the potential of GEE to support geospatial community is less well explored. Scientists are still waiting to see what public cloud platforms can do for geospatial web services. This paper proposes a prototype called WS4GEE that can wrap GEE-embedded datasets, functions, and models as OGC Web Services such as WMS, WFS, WCS, and WPS. In this way, WS4GEE can support direct access to GEE through OGC interfaces thus allowing geoprocessing workflows to use GEE resources. Two experiments are presented – one with a GEE-enabled geospatial data service and the other deploying geoprocessing composition with GEE-enabled GWSs. The results confirm that WS4GEE with the support of GEE significantly enhances the capabilities of GWS to deal with labor intensive and time-consuming tasks. This study provides guidance for the wider geospatial community when integrating other existing public cloud platforms. Highlights: First attempt to integrate Google Earth Engine (GEE) with geospatial web service community. WS4GEE facilitates the wrapping of GEE datasets, functions, and models as GEE-enabled OGC WMS, WFS, WCS, and WPS services. Enables the GEE to participate in geoprocessing workflow composition with other available geospatial web services. Several strategies are proposed to tackle constraints restricting the publication of GEE-enabled WCSs. Provides a simplified way for scientists to use GEE for environmental modeling.